The Nepalese Stock Market: Efficient and Calendar Anomalies - K.C., Fatta Bahadur; Joshi, Nayan Krishna (NRB Economic Review, 2005)
After describing the various forms of efficiency and calendar anomalies observed in many developed and emerging markets according to the existing literature, the present study examines this phenomenon empirically in the Nepalese stock market for daily data of Nepal Stock Exchange Index from February 1, 1995 to December 31, 2004 covering approximately ten years. Using regression model with dummies, we find persistent evidence of day-of-theweek anomaly but disappearing holiday effect, turn-of-the-month effect and time-ofthe- month effect. We also document no evidence of month-of-the-year anomaly and half-month effect. Our result for the month-of-the-year anomaly is consistent to the finding observed for the Jordanian stock market and that for the day-of-the-week anomaly to the Greek stock market .In addition, our finding regarding half-month effect is consistent with the US market. For the rest, we find inconsistent results with that in the international markets. Our results indicate that the Nepalese stock market is not efficient in weak form with regard to the day-of-the-week anomaly but weakly efficient with respect to the other anomalies.